2008
DOI: 10.5395/jkacd.2008.33.1.028
|View full text |Cite
|
Sign up to set email alerts
|

Stress distribution of Class V composite resin restorations: A three-dimensional finite element study

Abstract: This study was to investigate the influence of composite resins with different elastic modulus, cavity modification and occlusal loading condition on the stress distribution of restored notch-shaped noncarious cervical lesion using 3-dimensional (3D) finite element (FE) analysis.The extracted maxillary second premolar was scanned serially with Micro-CT. The 3D images were processed by 3D-DOCTOR. ANSYS was used to mesh and analyze 3D FE model. A notch-shaped cavity and a modified cavity with a rounded apex were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…Regarding this study, marginal discoloration results showed there are two restorations scored Bravo in the control group while three restorations scored bravo in the intervention group after 12 months with no significant difference between the restoration groups (p = 0.791), but there was a significant difference within ACTIVA group over the time (p = 0.05). This result is in acceptance with Park et al (2008) who attributed the difficulty of bonding to class V cavity to high flexural stresses on restoration that cause debonding [6]. Moreover, general difficulty in dentin bonding due to its heterogeneous structure, inherited wetness, collagentic activity of MMPS, and cysteine cathepsins.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Regarding this study, marginal discoloration results showed there are two restorations scored Bravo in the control group while three restorations scored bravo in the intervention group after 12 months with no significant difference between the restoration groups (p = 0.791), but there was a significant difference within ACTIVA group over the time (p = 0.05). This result is in acceptance with Park et al (2008) who attributed the difficulty of bonding to class V cavity to high flexural stresses on restoration that cause debonding [6]. Moreover, general difficulty in dentin bonding due to its heterogeneous structure, inherited wetness, collagentic activity of MMPS, and cysteine cathepsins.…”
Section: Discussionsupporting
confidence: 57%
“…Cervical lesions restorations are posing a challenge to the dental profession [6]. Cervical adhesive restorations failure is often attributed to inadequate moisture control, adhesion to different opposite substrates (enamel and dentin), differences in dentin composition, and great flexural stresses acting on the restoration that may lead to early loss or fracture [7].…”
Section: Introductionmentioning
confidence: 99%
“…If the modulus of elasticity of the core material is similar to the post material, a more uniform stress distribution within the entire post-and-core restoration and within dentin is achieved, while the restoration' s resistance is increased against the high forces of mastication 27,28) . As with many in vitro studies, it is difficult to extrapolate the results of this study directly to a clinical situation 29) . For example, the finish line and ferrule were placed at a constant height around the periphery of the teeth.…”
Section: ⅳ Discussionmentioning
confidence: 99%
“…Stress analysis was focused at the CEJ area of buccal and palatal surface based on the reports of many FEA studies 12,[23][24][25] . Kuroe et al 26) also confirmed by the photoelastic method that a vertical force loaded on the tooth causes stress concentration at the cervical line.…”
Section: ⅳ Discussionmentioning
confidence: 99%